Exploring the macro-level, meso-level and micro-level barriers and facilitators to the provision of good quality early inflammatory arthritis (EIA) care in England and Wales - Sam Norton; Cath Taylor; James Galloway; Magdalena Zasada; Mark Yates; Nicola Ayers; Zoë Ide (RMD Open)
Background Evidence from a national clinical audit of early inflammatory arthritis (EIA) shows considerable variability between hospitals in performance, unexplained by controlling for case-mix.Objective To explore the macro-level, meso-level and micro-level barriers and facilitators to the provision of good quality EIA care.Methods A qualitative study within 16 purposively sampled rheumatology units across England and Wales. Quality was assessed in relation to 11 quality indicators based on clinical opinion, evidence and variability observed in the data. Data from semi-structured interviews with staff (1–5 from each unit, 56 in total) and an online questionnaire (n=14/16 units) were integrated and analysed using the framework method for thematic analysis using a combined inductive and deductive approach (underpinned by an evidence-based framework of healthcare team effectiveness), and constant comparison of data within and between units and its relationship with the quality criteria.Findings Quality of care was influenced by an interplay between macro, meso and micro domains. The macro (eg, shared care arrangements and relationships with general practitioners) and meso (eg, managerial support and physical infrastructure) factors were found to act as crucial enablers of and barriers to higher quality service provision at the micro (team) level. These organisational factors directly influenced team structure and function, and thereby EIA care quality.Conclusions Variability in quality of EIA care is associated with an interplay between macro, meso and micro service features. Tackling macro and meso barriers is likely to have a significant impact on quality of EIA service, and ultimately patient experience and outcomes.